한의학 용어 수집 및 관리 시스템 구축 - 차승준; 김상균; 송미영; 최윤정; 엄동명; 이병욱; 이규철; Cha, Seung-Jun; Kim, Sang-Kyun; Song, Mi-Young; Choi, Yun-Jeong; Eom, Dong-Myung; et al. (대한예방한의학회지, 2010)
Background : The system for collecting and managing the terminologies of Korean oriental medicine is essential to facilitate researches of developing intelligent information architecture based on ontology. Objectives : The purpose of this paper is to develop system for collecting and managing system for terminologies of Korean oriental medicine. Methods : First we defined roles of users used in this system, and define the system workflow based on them. Then we developed web-based collecting and managing system in which multiuser can work simultaneously, and it is compose of relational database system. Results : The terminologies of Korean Oriental Medicine can be efficiently collected, purified, inspected, and utilized by using proposed system. Conclusions : The system, proposed in this paper, can be used the whole field of oriental medicines for basic technology and has great contributions to make intelligent information architecture of oriental medicine based on ontology concept.